2005
DOI: 10.1158/0008-5472.can-04-4458
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein 90 Inhibitor, 17-Allylamino-17-demethoxygeldanamycin, Enhances Osteoclast Formation and Potentiates Bone Metastasis of a Human Breast Cancer Cell Line

Abstract: Breast cancer metastasis to the bone occurs frequently, causing numerous complications including severe pain, fracture, hypercalcemia, and paralysis. Despite its prevalence and severity, few effective therapies exist. To address this, we examined whether the heat shock protein 90 (Hsp90) inhibitor, 17-allylamino-17-demethoxygeldanamycin (17-AAG), would be efficacious in inhibiting breast cancer metastasis to bone. Utilizing the human breast cancer subline, MDA-MB-231SA, previously in vivo selected for its enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
106
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 48 publications
8
106
0
1
Order By: Relevance
“…Each of the three inhibitors of osteoclastogenesis counteracted this activity. These data support and extend the results of a recent report in which 17-AAG was found to promote differentiation of preosteoclasts and to increase bone metastases in a murine breast cancer model (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Each of the three inhibitors of osteoclastogenesis counteracted this activity. These data support and extend the results of a recent report in which 17-AAG was found to promote differentiation of preosteoclasts and to increase bone metastases in a murine breast cancer model (18).…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Price et al (18), 17-AAG was reported to promote formation of osteolytic lesions and bone metastases in a murine breast cancer model (18). Because Src kinase is essential for osteoclast maturation (19,20), we examined the possibility that 17-AAG-induced Src activation in osteoclasts may mediate this phenomenon.…”
mentioning
confidence: 94%
“…But Hsp90 inhibitors such as geldanamycin and the ansamycin derivative 17-AAG have been reported to show other effects than tumor inhibition (Schumacher et al 2007). Several data demonstrated that GA pretreatment could induce cell protection (Price et al 2005;Gotz et al 2006). These results raise concerns about treating certain kinds of cancers with Hsp90 inhibitors and suggest that it will be important to understand the tissue-specific effects of Hsp90 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Although Srcdependent activation of Akt and Erk after GA is relatively short-lived, these data raise the concern that in certain contexts Hsp90 inhibition might favor tumor survival and͞or progression. Indeed, a recent study reported that 17-allylamino-17-demethoxygeldanamycin (17-AAG) promotes formation of osteolytic lesions and bone metastases in a murine breast cancer model by potentiating osteoclastic bone resorption, even though the drug reduced tumor growth at the orthotopic site (35). Because Src is essential for osteoclast activity (20) and Src-induced activation of Akt and Erk promotes osteoclast survival (36, 37), 17-AAG-induced Src activation, as described in this study, may be responsible for the reported effects of 17-AAG on bone.…”
Section: Discussionmentioning
confidence: 99%